Grid-Connected Renewable Energy Sources - Hernandez, J. C. (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
The use of renewable energy sources (RESs) is a need of global society. This editorial, and its associated Special Issue "Grid-Connected Renewable Energy Sources", offers a compilation of some of the recent advances in the analysis of current power systems that are composed after the high penetration of distributed generation (DG) with different RESs. The focus is on both new control configurations and on novel methodologies for the optimal placement and sizing of DG. The eleven accepted papers certainly provide a good contribution to control deployments and methodologies for the allocation and sizing of DG.